Work Meaningfulness as A Predictor Of Organizational Affective Commitment Among Nurses at Hospital A Bandar Lampung - Maulina, Delara Lika; Kusmaryani, Rosita Endang (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Affective commitment is an integral part of nurses' performance in terms of service quality in hospitals. However, the majority of nurses still tend to lack emotional involvement or attachment to the hospital. Therefore, it is important to understand the meaningfulness of work as a predictor of affective commitment in nurses. This study aims to identify the meaningfulness of work as a predictor of affective commitment in nurses at Hospital A, Bandar Lampung. This study used a quantitative approach with a survey method. The study was conducted at Hospital A Bandar Lampung. 137 nurses were the subjects of the study. Accidental sampling was used as the data collection technique. The instruments used were a 10-item work meaningfulness scale and an 8-item affective commitment scale, both of which were tested for validity and reliability. The reliability test for work meaningfulness was 0.87 and for affective commitment was 0.93. The content validity for work meaningfulness was 1 and for affective commitment was 0.62. The hypothesis testing used in this study was a multiple regression test. The overall analysis results showed that meaningfulness of work significantly predicts affective commitment by 38.2%. The partial data analysis results found that: 1) the dimension of positive meaning in work (x1) is a predictor of affective commitment by providing an effective contribution of 12.99%; 2) the dimension of meaning making through work (x2) is a predictor of affective commitment by providing an effective contribution of 12.57%; and 3) the dimension of greater good motivation (x3) is a predictor of affective commitment by providing an effective contribution of 12.46%.